Diaryl Ketones as Photoactivators - Perez-Prieto, J.; Galian, R. E.; Miranda, M. A. (Mini-Reviews in Organic Chemistry, 2006)
The lowest lying triplet excited states of diaryl ketones are usually long lived and can be photochemically generated with high quantum yields. Hence, compounds of this type are efficient triplet photosensitizers. Three major mechanisms, namely hydrogen abstraction, energy transfer and electron transfer, can be involved in the photosensitized processes. This paper reviews recent examples on the relevance of diaryl ketones as triplet photosensitizers in synthesis. In addition, a number of applications are also presented. In general, the literature coverage has been limited to the publications that appeared during the last five years.
Keywords: energy transfer and electron transfer